Application of the Discovery Learning Learning Model Assisted by Audio Visual Media on Respiratory System Material in Humans - Skilfre Julianty Pelleng; Arrijani Arrijani; Caroline Manuahe (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This study incorporates classroom action research as a means to ascertain the enhancement of student learning results. The participants in this study consisted of 29 students enrolled in the XI IPA class at SMA Negeri 1 Touluaan. The study was conducted over two cycles. The findings from the initial cycle of research indicated that the students' learning outcomes were fully achieved, with a completion rate of 51.72% or 15 students successfully completing their courses. In contrast, the findings of this study reveal that the implementation of the Discovery Learning model, supported by audio-visual media, in teaching the respiratory system in human biology can enhance the learning outcomes of 11th-grade students in SMA Negeri 1 Touluan.